Analisis dan Strategi Pengembangan Objek Wisata Pantai Batu Buaya di Desa Busisingo Kecamatan Tutuyan Kabupaten Bolaang Mongondow Timur - Ruslani; Marthen Tombeg; Sony Wijanarko; Bella Makaminang; Tesalonika Kaunang (Jurnal Ilmu Pariwisata, 2025)
The tourism industry is an important contributor to the global economy, generating revenue, employment opportunities, and infrastructure investment. The development of sustainable tourism is essential to preserve the environment and ensure social sustainability. This study aims to analyze and formulate development strategies for Batu Buaya Beach, a tourism destination located in East Bolaang Mongondow Regency, North Sulawesi, Indonesia. The research employed direct observation methods and interviews with the village head, local residents, beach managers, and tourists. The results indicate that the main strengths of Batu Buaya Beach include its natural beauty, unique rock formations, and relatively complete facilities. However, several weaknesses were identified, such as limited road access, suboptimal infrastructure management, and an unstable number of visitors. Opportunities for improvement include infrastructure development, ecotourism development, facility integration, and the utilization of existing facilities for ecotourism programs. The threats faced consist of competition with other tourist destinations, environmental degradation, and excessive dependence on investors. The proposed development strategies include prioritizing road access improvements, designing sustainable ecotourism programs, creating new attractions to stabilize visitor numbers, and developing unique ecotourism programs to increase tourist visits. This study concludes that Batu Buaya Beach has significant potential for tourism development.